Effect of Environmental Stress on the Nutrient Stoichiometry of the Clonal Plant Phragmites australis in Inland Riparian Wetlands of Northwest China - Zhou, Yi; Jiao, Liang; Qin, Huijun; Li, Fang (Frontiers in Plant Science, 2021)
Clonal plants play an important role in determining ecosystem properties such as community stability, species diversity and nutrient cycling. However, relatively little information is available about the stoichiometric characteristics of clonal plants and their drivers in inland riparian wetlands under strong environmental stress. In this paper, we studied the clonal plant Phragmites australis in an inland riparian wetland of Northwest China and compared its nutrient distribution and stoichiometry trade-offs as well as its responses to soil environmental factors in three different environments, namely, a wetland, a salt marsh, and a desert. We found that 1) P. australis could adapt to heterogeneous environments by changing its nutrient allocation strategies, as evidenced by the significant decrease in N and P contents and significant increase in whole-plant C:P and N:P ratios from the wetland to the desert habitats. 2) P. australis adapted to stressful environments by changing its nutrient allocation patterns among different modules, showing a greater tendency to invest N and P in underground modules (rhizomes and roots) and an increase in the utilization efficiency of N and P in the leaves and stems as environmental stress increased. 3) The C-N, C-P, and N:P-C in the whole plant and in each module showed significant anisotropic growth relationships in the three habitats (P<0.05). 4) Soil water, pH and salt were the main factors limiting nutrient stoichiometry. The results of this study clarified the ecological adaptation mechanism of the clonal plant P. australis to heterogeneous environments and provided targeted protection strategies for inland riparian wetlands in Northwest China.